Background readings in language teaching - Hemphill, Roderick J. (Quezon City, Philippines : Phoenix Publishing House, Inc., 1962)
The series of articles in the original edition of this monograph was intended to serve as background material for Filipino teachers interested in learning about modern methods of language teaching. In the revised edition the editor has sought to make the material presented also interesting and useful to teachers other than Filipinos, although the examples remain those of the Philippine language scene and the point of view that of American educators who have had the pleasure of working with Filipino teachers of English for over four years. The articles are primarily concerned with the problems of teaching English to speakers of Filipino languages, but the principles described apply equally well to any language teaching situation.
THE NATURE OF LANGUAGE -- THE MEANING OF SECOND LANGUAGE TEACHING -- THE CONCEPT OF PATTERN -- THE ANALYSIS OF A LANGUAGE - SOUNDS -- HOW CONSONANT SOUNDS ARE MADE -- ARTICULATION COMPARING TWO LANGUAGES TAGALOG AND ENGLISH -- THE VALUE OF CONTRASTIVE ANALYSIS -- THE NATURE AND USE OF A PHONEMIC TRANSCRIPTION -- A PEDAGOGICAL TRANSCRIPTION OF ENGLISH -- INTONATION IN ENGLISH -- STRESS IN ENGLISH -- STEPS IN READING ENGLISH.
Includes bibliographical references and index.
Keywords: LANGUAGE TEACHING